Specification of ACMG/AMP variant classification guidelines for Familial Hypercholesterolemia – a ClinGen FH Variant Curation Committee Pilot Study - Kurtz, C. Lisa (2019)
Familial hypercholesterolemia (FH) is a common autosomal dominant disorder (~1:250 individuals affected) of lipid metabolism, associated with an increased risk of cardiovascular disease. Individuals with FH characteristically present with severely elevated blood cholesterol levels, which leads to atherosclerotic plaque formation and subsequently, myocardial infarction due to premature coronary artery disease. Three main causative genes have been associated with FH: LDLR, APOB and PCSK9. Diagnosis is critical for early intervention and treatment, and it is imperative that family members of affected individuals be identified as early as possible.